Factors Affecting Adoption of Climate-smart Agriculture Practices: Evidence from Uttar Pradesh, India - Jatav, Surendra Singh (Indian Journal of Extension Education, 2024)
The study examined the determinants of climate-smart agriculture (CSA) practices in Uttar Pradesh. The systematically collected data of 480 sampled farmers from two regions of Uttar Pradesh, namely Central and Bundelkhand, was analysed using the binary logistic regression model. A field survey was conducted in August and September 2022. Farmers belonging to the Lucknow district were having relatively higher adoption rates of CSA practices. Entrepreneurial orientation (EO), consisting of risk-taking, innovativeness, and pro-activeness, was a significant factor influencing farmers’ adoption of CSA techniques. The findings show that male farmers are more inclined to use irrigation, certified seed, crop rotation, and soil testing. Education is linked to the acceptance of certified seed and soil testing, which necessitates financial commitment from farmers. Farmers, who have improved their irrigation facilities their income increased by 11.50 per cent, while those who had tested soil before plantation, the income increased by 54.76 per cent. Therefore, research indicates that entrepreneurship training and education courses for farmers should be customised to aspects of entrepreneurial orientation, such as risk-taking, innovativeness, and proactiveness.
Keywords: Binary logistic regression; Climate change; Climate adaptation; Climate-smart agriculture; Rainfed agriculture